Millennials’ Entrepreneurial Values, Entrepreneurial Symbiosis Network and New Ventures Growth: Evidence From China - Zhang, Ling; Zhou, Xue; Shirshitskaia, Ekaterina (Frontiers in Psychology, 2021)
The fate of new start-ups incubated by the same corporate ecosystem is different. Can entrepreneurs' ideas affect the way out of incubating companies? Based on self-verification theory and symbiosis theory, we took millennial entrepreneurs as the research object, combined with entrepreneurial enterprises' data in the makerspace. We analyzed the impact of millennials’ entrepreneurial values on new venture growth and explored the mediating role of entrepreneurial symbiosis networks. The following conclusions are obtained by analyzing the questionnaire of 191 millennial entrepreneurs: Millennials’ entrepreneurial values significantly promote new venture growth. The strength and scale of the entrepreneurial symbiosis network have a positive impact on new venture growth. The entrepreneur symbiosis network acts as an intermediary between the millennials’ entrepreneurial values and new venture growth.